Dialectical behavior therapy for Posttraumatic Stress Disorder (DBT-PTSD) compared with Cognitive Processing Therapy (CPT) in complex presentations of PTSD in women survivors of childhood abuse: a randomized clinical trial - Bohus, Martin; Kleindienst, Nikolaus; Hahn, Christopher; Müller-Engelmann, Meike; Ludäscher, Petra; Steil, Regina; Fydrich, Thomas; Kühner, Christine; Resick, Patricia A.; Stiglmayr, Christian; Schmahl, Christian; Priebe, Kathlen (JAMA psychiatry, 2020)
Childhood abuse significantly increases the risk of developing posttraumatic stress disorder (PTSD), often accompanied by symptoms of borderline personality disorder (BPD) and other co-occurring mental disorders. Despite the high prevalence, systematic evaluations of evidence-based treatments for PTSD after childhood abuse are sparse.To compare the efficacy of dialectical behavior therapy for PTSD (DBT-PTSD), a new, specifically designed, phase-based treatment program, against that of cognitive processing therapy (CPT), one of the best empirically supported treatments for PTSD.From January 2014 to October 2016, women who sought treatment were included in a multicenter randomized clinical trial with blinded outcome assessments at 3 German university outpatient clinics. The participants were prospectively observed for 15 months. Women with childhood abuse-associated PTSD who additionally met 3 or more DSM-5 criteria for BPD, including affective instability, were included. Data analysis took place from October 2018 to December 2019.Participants received equal dosages and frequencies of DBT-PTSD or CPT, up to 45 individual sessions within 1 year and 3 additional sessions during the following 3 months.The predefined primary outcome was the course of the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) score from randomization to month 15. Intent-to-treat analyses based on dimensional CAPS-5 scores were complemented by categorical outcome measures assessing symptomatic remission, reliable improvement, and reliable recovery.Of 955 consecutive individuals assessed for eligibility, 193 were randomized (DBT-PTSD, 98; CPT, 95; mean [SD] age, 36.3 [11.1] years) and included in the intent-to-treat analyses. Analysis revealed significantly improved CAPS-5 scores in both groups (effect sizes: DBT-PTSD: d, 1.35; CPT: d, 0.98) and a small but statistically significant superiority of DBT-PTSD (group difference: 4.82 [95% CI, 0.67-8.96]; P = .02; d, 0.33). Compared with the CPT group, participants in the DBT-PTSD group were less likely to drop out early (37 [39.0%] vs 25 [25.5%]; P = .046) and had higher rates of symptomatic remission (35 [40.7%] vs 52 [58.4%]; P = .02), reliable improvement (53 [55.8%] vs 73 [74.5%]; P = .006), and reliable recovery (34 [38.6%] vs 52 [57.1%]; P = .01).These findings support the efficacy of DBT-PTSD and CPT in the treatment of women with childhood abuse-associated complex PTSD. Results pertaining to the primary outcomes favored DBT-PTSD. The study shows that even severe childhood abuse-associated PTSD with emotion dysregulation can be treated efficaciously.German Clinical Trials Register: DRKS00005578
Gesehen am 01.02.2024